ORGANIZATIONAL VANDALISM: IDEA, TYPES, INDICATORS - I. A. Simonova; A. G. Obolenskaya (Дискурс)
The study aims to conceptualize socio-economic and philosophical dimensions of organizational vandalism phenomenon. This made it possible to distinguish its outlines in the perspective of relevant social processes and to define organizational vandalism more specifically as some dynamic social and economic interaction within an organization. It is difficult to investigate organizational vandalism as subjects of acts of vandalism, as well as owners and managers, try not to spread such information about the organization and their actions in case of vandalism. However, managers and line staff do not deny that abstract vandalism harms the organization, but they cannot fully assess its alternative consequences. As a result, the organization cannot optimize efforts to prevent employees’ property abuse at the workplace. The identified trends in the case of small and medium-sized business in Ekaterinburg show additional possibilities for its socio-economic and philosophical comprehension and for defining practical prospects of risk assessement for an organization.